Allowable Rates of Fluid Temperature Variations and Thermal Stress Monitoring in Pressure Elements of Supercritical Boilers. Issue 17 (8th November 2019) - Taler, Jan; Taler, Dawid; Kaczmarski, Karol; Dzierwa, Piotr; Trojan, Marcin; Jaremkiewicz, Magdalena
ABSTRACT: Allowable rates of fluid temperature changes in critical elements of supercritical steam boilers were determined assuming a quasi-steady state of temperature distribution in pressure components. A method was proposed for monitoring the thermal stresses in the critical pressure components.